The Åland Islands, Finland and European Security in the 21st Century - Heinikoski Saila (Åland Islands Peace Institute, 2022)
This article will review the Åland Islands in the European and Finnish security context. The Åland Islands is a demilitarised, neutralised and autonomous province of Finland, and the aim of the article is to look at how the more than 160-year old demilitarisation regime relates to the current security context. The time period to be examined is limited to the 21st century, encompassing deeper security cooperation of the European Union and debates on Finnish foreign policy in the European context as a non-NATO country. A major theme of the discussion is to look at the militarisation trends in Europe and how that might affect Finland and the Åland Islands. The article also touches upon topical issues such as Brexit, advancement of European security cooperation and Finnish NATO debates. It examines the demands for change concerning the status of the Åland Islands as well as how security is approached from the Ålandic perspective. Moreover, the issue of what could happen if Finland would join the NATO is discussed. The article concludes that the status appears to have very stable role stipulated in international law, despite securitising and militarising trends in the surrounding region. Indeed, a multilateral solution such as demilitarisation serves as a contrast to the regionalisation operating on military logic.